CASE REPORT ANESTHETIC MANAGEMENT OF ADRENAL TUMOR RESECTION - Widnyana, I Made Gede; Putra, Kadek Agus Heryana; Kurniyanta, Putu; Suarjaya, I Putu Pramana; Suranadi, I Wayan; Hartono, Budi (Bali Journal of Anesthesiology, 2018)
ABSTRACTThe adrenal glands are secretory organs that are located above each kidney and produce hormones that play a major role in the metabolic processes. Tumors of the adrenal gland can cause metabolic abnormalities associated with hormonal disorders such as Cushings syndrome, pheochromocytoma, or Conns syndrome. To be able to give a good anesthetic management on resection of the adrenal tumor, it requires adequate preoperative evaluation. However, this will take large resources. Management of anesthesia in adrenal tumor with an unknown hormonal disorder should consider a variety of hormonal abnormalities that may present in the patient so it can be anticipated effectively.Keywords: incidentaloma, adrenalectomy, hormonal disorder, perioperative